Biappositives: A New Appellation of Appositives - Gunawan, Hero; CM. Simatupang, Ervina; Sari, Puspita; T. Bungaran Siregar, Alvii (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses biappositives as the new appellation in both restrictive and non-restrictive appositives. In every single apposition construction, an anchor does not always have one appositive. This type of appositive will be viewed from a syntactic perspective. From this perspective, this article will uncover that 1) one anchor, in a construction of apposition, may have two appositives, and each appositive has its own name, depending on the relatedness to the anchor, i.e., external biappositive, internal-external biappositive, external-relational biappositive, and external-integral biappositive; 2) the sequential patterns of apposition construction. Therefore, this research serves two aims: 1) to explain and indicate that an anchor may have two appositives with different names, and 2) to analyse the sequential patterns of apposition constructions. The data sources are taken from three English printed media: 1) daily news The JaACrta Post, 2) weekly magazine TIME, and 3) monthly magazine Reader’s Digest. The data taken from such sources are descriptive in nature and will be analysed through employing the method of qualitative research. To analyse such descriptive data, the distributional method of analysis involves the use of the following techniques: deleting, extracting, and intruding. The results indicate that: 1) biappositive is a new appellation of appositive in a construction of apposition with the following subcategories: external appositive, internal-external appositive, external-relational appositive, and external-integral appositive; 2) the sequential patterns of apposition constructions are: a) … A1, A2, A3 for external biappositive; b) … A1 A2, A3 for internal external biappositive; c) … A1, A2, A3 and/or A1, A2, A3 … for external-relational biappositive; and d) A1, A2 A3 … for external-integral biappositive.